Investigation on upscaling selective laser melting process parameters using 17-4 PH stainless steel powder - Makoana, Nkutwane Washington (Bloemfontein: Central University of Technology, Free State, 2018)
The use of Additive Manufacturing processes, like Selective Laser Melting, is gaining popularity in the manufacturing industry. This is due to its attractive benefits such as high geometrical flexibility and agile response to customisation. Unlike traditional manufacturing processes like casting and forging, which depend on patterns and dies to manufacture the parts, additive manufacturing processes produce parts directly from a three-dimensional computeraided drawing of the part. The part is built using a laser beam and powder material layer by layer, thus drastically reducing the pre-processing time. Despite all the advantages of Additive Manufacturing, several challenges still remain to be overcome. One major drawback is that the actual production of parts is slow, with jobs taking one week or longer to complete. Therefore, improving the build rates of the current state-of-the-art additive manufacturing machines is inevitable. Literature reveals that the build rates of additive manufacturing processes can be potentially improved by using high-powered lasers with increased focused spot-size diameter in order to melt multiple layers at the same time. This study aims to investigate the aspects of upscaling selective laser melting process parameters on the characteristics of single tracks formed using different parametric combinations. For that purpose, two machines operating at different spot sizes and laser powers were used to produce the single tracks. The surface morphology and melt pool profiles were examined following standard metallographic examination techniques. The hardness was measured on the polished surface of the melt pool and the substrate material. The results obtained show that it is possible to produce continuous tracks using high laser powers and larger spot size. However, it was also observed that the maximum optimal scanning speed is higher when using a smaller spot size, and narrows down when using a larger spot size. There was no significant variation in the hardness of the solidified melt pool for different parametric combinations. Also, the hardness of the solidified tracks was found to be comparable to the hardness of the substrate material.
Published Thesis